Effectiveness Program for Women Head of Family (PEKKA) In Sukabumi City - Annisa Ratu Fauziah; Dine Meigawati; Andi Mulyadi (Publik : (Jurnal Ilmu Administrasi), 2023)
One effort to empower a woman with a special to woman head family is the PEKKA program. The PEKKA program began with many activity themes, including microfinance institutions, micro, small businesses, and strengthening the law for justice, lifelong education, the right to strengthen a political position, and the right to public health. In implementing family development policies by implementing efforts to eradicate poverty, especially for women heads of families, empowerment of women is carried out, one of which is the holding of a program for women heads of families or commonly called PEKKA. The purpose of this study was to determine how far the effectiveness of the Women Heads of Family Program in Sukabumi City has been. There are 4 dimensions in the theory used, namely the accuracy of program targets, program socialization, achievement of program goals, and program monitoring. the method used in this study is a qualitative method using a descriptive approach. With interview data collection techniques, observation and documentation. The results showed that the effectiveness of the women-headed household empowerment program was not yet effective because it had not yet maximally achieved the success objectives of the female-headed household empowerment program (PEKKA), it was still not optimal in achieving program targets, and the socialization carried out to the wider community was not evenly distributed. Lack of improvement in the behavior of both knowledge and ability in-group members.